Prohibition of propaganda of non-procreation in the Russian Federation: Problems of normative legal regulation - Karamysheva, Maria S. (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право»)
Introduction. The protection of the family, motherhood, and childhood is one of the priorities of the policy of the modern Russian state. This is directly indicated by the content of Article 38 of the Constitution of the Russian Federation. In other domestic legal acts, the legal mechanisms of this protection are consolidated. In a similar vein, today we should consider the prohibition of propaganda of non-procreation, established in paragraph 1 of art. 6.21 of the Administrative Code of the Russian Federation. This ban was established in order to overcome the difficult demographic situation that currently exists in the Russian Federation, as well as in the context of the need to implement a state policy to protect traditional family values in the Russian Federation. Theoretical analysis. The study of approaches regarding the content of the category of "refusal to procreate" in the above-mentioned norm reveals that this definition can be perceived in different ways: as adherence to the "childfree" or "child hate" belief system and as one’s own conscious choice of not wanting to have children (voluntary childlessness). In this regard, the question arises: the prohibition of propaganda of what views is being discussed in the context of the current version of paragraph 1 of Article 6.21 of the Administrative Code of the Russian Federation. Empirical analysis. The analysis of p. 1 of Article 6.21 of the Administrative Code of the Russian Federation demonstrates the lack of specific criteria for the promotion of non-procreation. In addition, there is no special regulatory legal act at the federal legislative level that would regulate this aspect. Results. Signs of propaganda against procreation, which is subject to prohibition in accordance with clause 1 of Article 6.21 of the Administrative Code of the Russian Federation, have been proposed. Among other things, it has been proposed to establish a regulatory ban on propaganda aimed at inciting hatred against people having children or intending to become parents in the future.